A blackening process for improving the conductivity of lithium tantalate wafers

By using spherical copper powder, modified graphene and sheet copper powder as composite reducing agents, the conductivity of lithium tantalate wafers is improved, and the problem of electrostatic charge accumulation in the heating process of lithium tantalate crystals is solved, and the conductivity is significantly improved and the pyroelectric effect is improved.

CN119392379BActive Publication Date: 2025-03-21HUNAN INSTITUTE OF ENGINEERING +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411987382.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Lithium tantalate crystals are prone to form static charges during heating, resulting in pyroelectric effect and damaging the wafer and interdigital electrodes. The prior art is difficult to effectively solve this problem.

Method used

Spherical copper powder, modified graphene and sheet copper powder with mass ratio of 1: (0.1~0.2): (0.5~2) are used as composite reducing agents to increase the conductivity of lithium tantalate wafers through heat treatment and reduce the pyroelectric effect.

Benefits of technology

It significantly reduces the resistivity of lithium tantalate wafers, improves the conductivity, improves the pyroelectric effect, and extends the service life of the wafer and electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392379B_ABST
    Figure CN119392379B_ABST
Patent Text Reader

Abstract

The invention discloses a blackening treatment process for the electrical conductivity of a lithium tantalate wafer, belonging to the technical field of crystal materials. The blackening treatment process for the electrical conductivity of a lithium tantalate wafer comprises the following steps: spreading a composite reducing agent on the bottom of a crucible to form a bottom reducing agent layer, placing a lithium tantalate wafer on the bottom reducing agent layer, and then spreading the composite reducing agent on the lithium tantalate wafer to form a top reducing agent layer; introducing nitrogen for heat treatment, taking it out, and obtaining a blackened lithium tantalate wafer; the composite reducing agent comprises spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2). A blackening treatment process for the electrical conductivity of a lithium tantalate wafer, the blackening treatment process of the invention can significantly reduce the resistivity of the lithium tantalate wafer, improve the electrical conductivity of the lithium tantalate wafer, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystal materials, and in particular to a blackening process for improving the electrical conductivity of lithium tantalate wafers. Background Art

[0002] Lithium tantalate crystals (LiTaO3) have excellent and stable piezoelectric, ferroelectric, and pyroelectric properties, and are widely used in surface acoustic wave (SAW) devices and infrared detection devices.

[0003] Surface acoustic wave devices and high-frequency broadband filters using lithium tantalate crystals as substrate materials need to be heated during the production process, which will inevitably cause changes in the temperature of the lithium tantalate crystals. The high pyroelectric coefficient of lithium tantalate crystals will trigger a pyroelectric effect due to temperature changes, making it easy for a large amount of static charge to form on the surface of the chip. These charges will be released spontaneously between the interdigital electrodes and between the chips. It is easy to damage the chip or even burn the interdigital electrodes, especially when making fine interdigital electrodes for high-frequency SAW filters. The charge accumulation caused by the pyroelectric effect of lithium tantalate crystals can cause damage to the substrate or even burn it. The blackening process can effectively improve the conductivity.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a blackening treatment process for the electrical conductivity of a lithium tantalate wafer. The blackening treatment process described in the present invention can significantly reduce the resistivity of the lithium tantalate wafer and improve the electrical conductivity of the lithium tantalate wafer, and has broad application prospects.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0008] The composite reducing agent is spread on the bottom of the crucible to form a bottom reducing agent layer, the lithium tantalate wafer is placed on the bottom reducing agent layer, and the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer; nitrogen is introduced for heat treatment, and the wafer is taken out to obtain a blackened lithium tantalate wafer;

[0009] The composite reducing agent comprises spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2).

[0010] The present invention creatively uses spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2) as a composite reducing agent, spreads them on the upper and lower sides of a lithium tantalate wafer, and then performs heat treatment, which effectively improves the electrical conductivity of the lithium tantalate crystal, effectively reduces the electric field generated on the crystal surface, improves the pyroelectric effect, and has broad application prospects.

[0011] The present invention uses spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2) as a composite reducing agent, and subjecting the lithium tantalate wafer to the above-mentioned specific reduction treatment, which can improve the valence state change of some ions in the lithium tantalate wafer, resulting in an increase in the number of free valence state electrons. These free electrons can move under the action of an external electric field, neutralize the charge generated by the pyroelectric effect, and reduce the pyroelectric effect.

[0012] Among them, the modified graphene can not only improve the reduction activity of the composite reducing agent, improve the interaction with lithium tantalate, and promote the blackening reaction, but also convert the phenolic resin into hard carbon with strong reducing properties at high temperature, effectively improve the reduction performance, further improve the reaction activity, improve the overall reaction efficiency, and can be in close contact with the lithium tantalate wafer. Among them, the spherical copper powder has high dispersibility and fluidity, which helps to be evenly distributed on the surface of lithium tantalate. The flaky copper powder has a larger specific surface area and provides more reaction sites. The spherical copper powder, modified graphene and flaky copper powder form a uniform mesh reduction network structure on the surface of lithium tantalate, which effectively improves the conductivity of the lithium tantalate crystal.

[0013] Studies have shown that the structure of lithium tantalate (LiTaO3) crystals can be viewed as a stack of oxygen octahedrons, in which lithium oxygen octahedrons and tantalum oxygen octahedrons are interconnected by shared oxygen ions. + and Ta5 + There is a difference in the binding strength between ions and oxygen ions, the Li-O bond is relatively weak, while the Ta-O bond is relatively strong. This structural feature makes it easy for lithium tantalate crystals to undergo specific chemical changes during the reduction process. The present invention uses spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1~0.2): (0.5~2) as a composite reducing agent. Under the specific method of the present invention, it can promote the escape of some oxygen atoms in the lithium tantalate crystal in gaseous form. At the same time, during the reduction process, the oxygen atoms are moved or replaced from the lithium tantalate lattice position, increasing oxygen vacancies to a certain extent, thereby improving the conductivity of the lithium tantalate wafer.

[0014] As a preferred embodiment of the present invention, the composite reducing agent comprises spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.14-0.18): (0.8-1.2).

[0015] As a preferred embodiment of the present invention, the average particle size of the spherical copper powder is 0.1-0.5 μm.

[0016] As a preferred embodiment of the present invention, the particle size of the flaky copper powder is 5-15 μm.

[0017] As a preferred embodiment of the present invention, the method for preparing the modified graphene comprises the following steps:

[0018] dispersing graphene and oxalic acid in a nitric acid solution to obtain a graphene dispersion;

[0019] The phenolic resin is heated to 120-150° C., a silane coupling agent is added, and then a graphene dispersion is added, the mixture is stirred evenly, and dried to obtain modified graphene.

[0020] As a preferred embodiment of the present invention, the mass ratio of the graphene, oxalic acid and nitric acid solution is 1: (0.05-0.1): (4-10);

[0021] The molar concentration of the nitric acid solution is 0.1-0.6 mol / L.

[0022] As a preferred embodiment of the present invention, the mass ratio of the phenolic resin, the silane coupling agent, and the graphene dispersion is 1: (0.02-0.06): (10-20).

[0023] As a preferred embodiment of the present invention, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0024] As a preferred embodiment of the present invention, the thickness of the bottom reducing agent layer is 3-5 mm; the thickness of the top reducing agent layer is 1-2 mm.

[0025] As a preferred embodiment of the present invention, the thickness of the lithium tantalate wafer is 0.2-0.3 mm.

[0026] As a preferred embodiment of the present invention, the heat treatment temperature is 900-1000° C., and the heat treatment time is 20-24 hours.

[0027] The beneficial effects of the present invention are as follows: (1) the present invention uses spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2) as a composite reducing agent, spreads them on the upper and lower sides of a lithium tantalate wafer, and then performs heat treatment, which effectively improves the conductivity of the lithium tantalate crystal, effectively reduces the electric field generated on the crystal surface, improves the pyroelectric effect, and has broad application prospects.

[0028] (2) The modified graphene described in the present invention can not only improve the reduction activity of the composite reducing agent, enhance the interaction with lithium tantalate, and promote the blackening reaction, but also, at high temperature, convert the phenolic resin into hard carbon with strong reducing properties, effectively improve the reduction performance, further enhance the reaction activity, and improve the overall reaction efficiency. It can be in close contact with the lithium tantalate wafer. Among them, the spherical copper powder has high dispersibility and fluidity, which helps to be evenly distributed on the surface of lithium tantalate. The flaky copper powder has a larger specific surface area and provides more reaction sites. The spherical copper powder, modified graphene and flaky copper powder form a uniform mesh reduction network structure on the surface of lithium tantalate, which effectively improves the conductivity of the lithium tantalate crystal. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Dimensions of the lithium tantalate wafer and crucible of the present invention.

[0030] Figure 2 This is a diagram showing the coverage of the composite reducing agent of the present invention on a lithium tantalate wafer. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0032] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0033] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0034] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0035] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0036] Lithium tantalate chip: Sourced from Hunan Kexintai Electronics Co., Ltd.

[0037] Spherical copper powder-1: The average particle size is 0.1 μm, from Xiangtian Nano, brand XT-Cu-03.

[0038] Spherical copper powder-2: The average particle size is 0.5 μm, from Xiangtian Nano, brand XT-Cu-05.

[0039] Spherical copper powder-3: The average particle size is 0.05 μm, from Xiangtian Nano, brand XT-Cu-01.

[0040] Spherical copper powder-4: The average particle size is 1 μm, from Xiangtian Nano, brand XT-Cu-06.

[0041] Flake copper powder-1: The average particle size is 5 μm, from Xiangtian Nano, brand XT-Cu-09.

[0042] Flake copper powder-2: The average particle size is 15 μm, from Xiangtian Nano, brand XT-Cu-10.

[0043] Flake copper powder-3: The average particle size is 1 μm, from Xiangtian Nano, brand XT-Cu-08.

[0044] Flake copper powder-4: The average particle size is 25 μm, from Xiangtian Nano, brand XT-Cu-11.

[0045] Phenolic resin: from Hebei Zetian Chemical, brand PF9182.

[0046] Graphene: Sourced from Xiamen Kaina Graphene, brand name KNG-G2.

[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0048] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0049] Example 1

[0050] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0051] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0052] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0053] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0054] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0055] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0056] (4) If Figure 2 As shown, the composite reducing agent is spread on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0057] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0058] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0059] Example 2

[0060] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0061] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0062] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0063] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0064] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0065] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.18:1.8 to obtain a composite reducing agent;

[0066] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0067] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0068] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0069] Example 3

[0070] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0071] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0072] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0073] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0074] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0075] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.1:2 to obtain a composite reducing agent;

[0076] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0077] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0078] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0079] Example 4

[0080] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0081] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0082] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0083] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0084] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0085] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.2:0.5 to obtain a composite reducing agent;

[0086] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0087] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0088] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0089] Example 5

[0090] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0091] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0092] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0093] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0094] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0095] (3) mixing spherical copper powder-2, modified graphene and flake copper powder-2 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0096] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0097] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0098] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0099] Example 6

[0100] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0101] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0102] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0103] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0104] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0105] (3) mixing spherical copper powder-3, modified graphene and flake copper powder-3 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0106] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0107] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0108] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0109] Example 7

[0110] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0111] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0112] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0113] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0114] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0115] (3) mixing spherical copper powder-4, modified graphene and flake copper powder-4 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0116] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 4 mm;

[0117] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1.5 mm;

[0118] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0119] Example 8

[0120] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0121] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0122] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0123] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0124] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0125] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0126] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 3 mm;

[0127] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 1 mm;

[0128] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0129] Example 9

[0130] A blackening process for improving the conductivity of lithium tantalate wafers comprises the following steps:

[0131] (1) Cut a 6-inch lithium tantalate wafer 1 into square lithium tantalate wafers of 10*10*0.288 mm;

[0132] Provide a cylindrical crucible 2 with a diameter of 15 mm, such as Figure 1 As shown, Figure 1 Dimensional drawings of lithium tantalate wafers and cylindrical crucibles;

[0133] (2) dispersing graphene and oxalic acid in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1:0.08:5;

[0134] The phenolic resin is heated to 140° C. and kept warm, γ-aminopropyltriethoxysilane is added, and then a graphene dispersion is added, and the mixture is stirred evenly at a speed of 200 rpm and dried to obtain modified graphene; the mass ratio of the phenolic resin, γ-aminopropyltriethoxysilane, and graphene dispersion is 1:0.05:14.

[0135] (3) mixing spherical copper powder-1, modified graphene and flake copper powder-1 in a mass ratio of 1:0.14:1.2 to obtain a composite reducing agent;

[0136] (4) spreading the composite reducing agent on the bottom of the crucible to form a bottom reducing agent layer 3, wherein the thickness D1 of the bottom reducing agent layer is 6 mm;

[0137] A lithium tantalate wafer is placed on the bottom reducing agent layer, and then the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer 4; the thickness D2 of the top reducing agent layer is 2 mm;

[0138] Nitrogen was introduced, and the temperature was raised to 1000° C. at a heating rate of 10° C. / min. Heat treatment was performed at 1000° C. for 24 hours, and the wafer was taken out to obtain a blackened lithium tantalate wafer.

[0139] Comparative Example 1

[0140] The difference between Comparative Example 1 and Example 1 is that the composition of the composite conductive agent is different, and this comparative example does not contain modified graphene, and the other aspects are the same.

[0141] The composite conductive agent of this comparative example includes spherical copper powder-1 and flaky copper powder-1 in a mass ratio of 1:1.2.

[0142] Comparative Example 2

[0143] The difference between Comparative Example 2 and Example 1 is that the composition of the composite conductive agent is different. In this comparative example, graphene is used to replace the modified graphene, and the other aspects are the same.

[0144] The composite conductive agent of this comparative example includes spherical copper powder-1, graphene and flaky copper powder-1 in a mass ratio of 1:0.14:1.2.

[0145] Comparative Example 3

[0146] The difference between Comparative Example 3 and Example 1 is that the preparation method of the modified graphene is different, and the other aspects are the same.

[0147] The composite conductive agent of this comparative example includes spherical copper powder-1, modified graphene and flaky copper powder-1 in a mass ratio of 1:0.14:1.2.

[0148] The preparation method of the modified graphene in this comparative example is:

[0149] Graphene and oxalic acid are dispersed in a 0.2 mol / L nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid and nitric acid solution is 1:0.08:5, γ-aminopropyltriethoxysilane is added, stirred evenly at a speed of 200 rpm, and dried to obtain modified graphene; the mass ratio of the γ-aminopropyltriethoxysilane to the graphene dispersion is 0.05:14.

[0150] Comparative Example 4

[0151] The difference between Comparative Example 4 and Example 1 is that the composition of the composite conductive agent is different, and the conductive agent of this comparative example does not contain flaky copper powder, and the other aspects are the same.

[0152] The composite conductive agent of this comparative example includes spherical copper powder-1 and modified graphene in a mass ratio of 1:0.14.

[0153] Comparative Example 5

[0154] The difference between Comparative Example 5 and Example 1 is that the composition of the composite conductive agent is different, and the conductive agent of this comparative example does not contain spherical copper powder, and the other parts are the same.

[0155] The composite conductive agent of this comparative example includes modified graphene and flaky copper powder-1 in a mass ratio of 0.14:1.2.

[0156] Test Case

[0157] The ST2643 ultra-high resistance micro-current tester (high resistance volume resistivity surface resistivity tester) uses the principle of the ring three-electrode method. The volume resistivity of the lithium tantalate wafer after electro-blackening is obtained, where ρ is the volume resistivity (Ω·cm), L is the wafer thickness, S is the contact area, and R is the volume resistance value of the lithium tantalate wafer after blackening. Apply a voltage source Vs to the upper electrode, specify the current flowing through the blackened lithium tantalate sample to be Im, and then the volume resistance R can be calculated using the formula Find R.

[0158] Table 1

[0159]

[0160] It can be seen from Table 1 that the blackening process described in the present invention can significantly reduce the resistivity of the lithium tantalate wafer and improve the conductivity of the lithium tantalate wafer, and has broad application prospects.

[0161] By comparing Example 1 with Comparative Examples 1 to 5, it can be clearly seen that the spherical copper powder, modified graphene and flaky copper powder described in the present invention as a composite reducing agent can significantly improve the conductivity of the lithium tantalate wafer, and the spherical copper powder, modified graphene and flaky copper powder have a significant synergistic effect.

[0162] It can be seen from the comparison of Examples 1 to 4 that the conductivity of the lithium tantalate wafer is further improved by controlling the mass ratio of the spherical copper powder, the modified graphene and the flaky copper powder to be 1: (0.14 to 0.18): (0.8 to 1.2).

[0163] By comparing Examples 1 and 5 to 7, it can be seen that by controlling the average particle size of the spherical copper powder to 0.1 to 0.5 μm and the particle size of the flake copper powder to 5 to 15 μm, the conductivity of the lithium tantalate wafer is further improved.

[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A blackening process for improving the conductivity of lithium tantalate wafers, characterized in that: The following steps are involved: The composite reducing agent is spread on the bottom of the crucible to form a bottom reducing agent layer, the lithium tantalate wafer is placed on the bottom reducing agent layer, and the composite reducing agent is spread on the lithium tantalate wafer to form a top reducing agent layer; Passing nitrogen gas for heat treatment, taking out, and obtaining a blackened lithium tantalate wafer; The composite reducing agent comprises spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.1-0.2): (0.5-2); The preparation method of the modified graphene comprises the following steps: Dispersing graphene and oxalic acid in a nitric acid solution to obtain a graphene dispersion; the mass ratio of the graphene, oxalic acid, and nitric acid solution is 1: (0.05-0.1): (4-10); The phenolic resin is heated to 120-150° C., a silane coupling agent is added, and then a graphene dispersion is added, stirred evenly, and dried to obtain modified graphene; the mass ratio of the phenolic resin, the silane coupling agent, and the graphene dispersion is 1: (0.02-0.06): (10-20).

2. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The composite reducing agent comprises spherical copper powder, modified graphene and flaky copper powder in a mass ratio of 1: (0.14-0.18): (0.8-1.2).

3. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The average particle size of the spherical copper powder is 0.1-0.5 μm.

4. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The particle size of the flaky copper powder is 5-15 μm.

5. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The molar concentration of the nitric acid solution is 0.1-0.6 mol / L.

6. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The silane coupling agent includes at least one of γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane.

7. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The thickness of the bottom reducing agent layer is 3-5 mm; the thickness of the top reducing agent layer is 1-2 mm.

8. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The thickness of the lithium tantalate wafer is 0.2-0.3 mm.

9. The blackening process for improving the conductivity of lithium tantalate wafer according to claim 1, characterized in that: The heat treatment temperature is 900-1000° C., and the heat treatment time is 20-24 hours.

Citation Information

Patent Citations

  • Blackening method of lithium niobate or lithium tantalate wafer

    CN110835781A

  • Blackening treatment method for improving conductivity of lithium niobate or lithium tantalate wafer

    CN114959907A